Description of macroscopic changes in composite resin disks subjected to high temperatures for forensic purposes - Arcos-Tulcán, Carlos; Díaz-González, Juan David; Canencio-Rodríguez, Kenny; Rodríguez-Meléndez, Diana; Viveros-Rebolledo, Carlos; Vega-Betancourt, Jonathan; Sepúlveda-Navarro, Wilmer; Sinisterra, Gustavo; Moreno-Gómez, Freddy (Revista Facultad de Odontología Universidad de Antioquia, 2016)
Introduction: the objective of this study was to analyze the behavior of 375 composite resin disks of five commercial systems (Z100 3M-ESPE®, Z250 3M-ESPE®, Z350 3M-ESPE®, Brilliant NG Coltene-Whaledent® and TPH3 Dentsply®) and five colors (A1, A2, A3, A3.5 and B2) when subjected to the action of high temperatures (200, 400, 600, 800 and 1000° C), in order to establish parameters to be implemented in methods of forensic dental identification in the case of burned, charred, or incinerated corpses or human remains. Methods: a descriptive pseudoexperimental in vitro study describing the macroscopic physical changes on the surface of composite resin disks subjected to high temperatures. Results: composite resin is highly resistant to high temperatures with no significant changes in macrostructure. These characteristic repetitive physical changes, such as dimensional stability, texture, color, fissures and cracks, fracture and shattering occur in specific temperature ranges in disks of different manufacturers. Conclusions: describing the behavior of composite resin in the presence of high temperatures can help guide the process of identification of individuals whose bodies have been subjected to the action of fire during the ante-post mortem comparisons. The in vitro information obtained in this study shows that the description of composite resin restorations is useful in forensic autopsy in the case of burned, charred, or incinerated corpses or human remains.